Teacher professional development and pedagogical skills as correlates of secondary school students' achievement in english language in Ibadan metropolis (2016)
The study examined the contributions of teachers 'professional development and pedagogical skills on secondary school students' achievement in English Language. It also investigated the nature and direction of relationship among teacher professional development, pedagogical skills and students' achievement in English Language. The study determined which variable (teacher development or pedagogical skills) significantly predict student's achievement in English language. This is a correlational study with the targeted population of all secondary school students in Ibadan metropolis. Two educational zones were purposively selected out of which ten secondary schools were randomly selected, 24 participants were also selected from each of the schools to make a total sample of 240 participants. Two instruments were used for data collection in the study namely; “English Language Achievement Test (ELAT)" r=0.85 and “Teachers' development and Pedagogical Skills Scale (TDPSS) " r=0. 75. The findings revealed that both teacher professional development and pedagogical skills jointly and significantly contributed to student's English Language achievement F(2,37)-6.797, p<0.05, Furthermore, only pedagogical skills relatively and significantly